Extracorporeal membrane therapy in a case of ruptured abscess on the mitroaortic intervalvular fibrosa associated to multisystem inflammatory syndrome: a case report - Lina P. Montaña-Jimenez; Ana M. Aristizabal; Carlos A. Guzmán-Serrano; Cesar Cely Reyes; Juan Fernando Vélez Moreno; Gastón Castillo (The Egyptian Heart Journal)
Abstract Background The mitroaortic intervalvular fibrosa is an avascular structure near the left ventricular outflow tract, between the mitral and aortic valves. Mitroaortic intervalvular fibrosa complications, such as tamponade, hemopericardium, and abscesses, are rare and often diagnosed postmortem. On the other hand, the COVID-19 pandemic notably impacted pediatric patients with congenital heart diseases, who frequently presented cardiac complications including arrhythmias, elevated troponins, myocarditis, and heart failure. However, the rupture of the mitroaortic intervalvular fibrosa kept being unusual, making this case a rare presentation of a COVID-19 complication. The objective of this text is to present an infrequent presentation of COVDI-19 complications, and the approach given at our institution which proved to be effective, and further supports the positive findings described in the literature regarding the utility of extracorporeal hemofiltration membranes. Case presentation A case of 15-year-old female, without any prior risk factors or cardiac comorbilities, who developed acute myocarditis, linked to COVID-19 Multisystem Inflammatory Syndrome is presented. She deteriorated despite adequate treatment, presenting mitroaortic intervalvular fibrosa rupture, leading to urgent surgical repair and requiring extracorporeal membrane hemofiltration for cytokine removal, therapeutic approach that proved to be effective. Postoperatively, she received intensive care and antibiotics, showing significant cardiac improvement. Noteworthy, hemofiltration was crucial in managing the cytokine storm, contributing to her recovery and subsequent discharge for continued medical management. Conclusion An abscess of the mitroaortic intervalvular fibrosa, though rare, represents a significant challenge to clinicians to diagnose. In patients with a history of COVID-19, especially when multisystem inflammatory syndrome is suspected, thorough evaluation is warranted to rule out cardiovascular complications, even in the absence of pre-existing cardiac conditions. This case contributes to our evolving understanding of the cardiovascular implications of COVID-19 and underscores the potential utility of various approaches, including the use of filtration membrane technologies.